Contribution of Interleukin-10-592 (-590, -597) C>A Polymorphisms to Periodontitis Susceptibility: An Updated Meta-Analysis Based on 18 Case-Control Studies. (19th September 2018) - Li, Yao; Feng, Ge; Deng, Yuejia; Song, Jinglin
Abstract : Introduction . The association between interleukin-10- (IL-10-) 592 (-590, -597) C>A polymorphisms and susceptibility to chronic or aggressive periodontitis (CP or AgP) is conflicting. This meta-analysis is aimed at quantitatively estimating the association. Materials and Methods . PubMed, Embase, Web of Science, and WANFAN were searched for studies performed prior to January 31, 2018, to collect data for our research. Meta-analysis was performed using RevMan 5.3 or STATA 14.0. Results . In total, 18 studies that met our criteria were included. Overall or HWE subgroup analysis of individuals with this polymorphism revealed that in terms of CP susceptibility, there was a significant difference between case groups and control groups in the A allele versus C allele model (OR = 1.38, 95% CI = 1.17–1.64 or OR = 1.38, 95% CI = 1.12–1.70), in the AA versus CC+CA model (OR = 1.49, 95% CI =1.06–2.10 or OR = 1.42, 95% CI = 1.13–1.78), and in the CC versus CA+AA model (OR = 0.69, 95% CI = 0.51–0.92 or OR = 0.68, 95% CI = 0.49–0.93); subgroup analysis based on a nonsmoking population also displayed significance in the A allele versus C allele model (OR = 1.43, 95% CI = 1.15–1.79) and CC versus CA+AA model (OR = 0.62, 95% CI = 0.44–0.87). For this polymorphisms and AgP susceptibility, our analyses revealed a significant association in both the A allele versus C allele model (OR = 1.29, 95% CI = 1.01–1.63) and the AA versus CC+CA model (OR = 1.93, 95% CI = 1.30–2.89); subgroup analysis based on Caucasian or nonsmoking populations showed significant differences in the AA versus CC+CA model (OR = 6.29, 95% CI = 1.78–22.21 or OR = 3.24, 95% CI = 1.59–6.61). Conclusions . IL-10-592 (-590, -597) A allele and the associated AA genotype may be risk factors for the onset of CP or AgP—particularly for the AA genotype and the increased risk of AgP in Caucasian or nonsmoking populations. Conversely, the CC genotype may act as a protective factor against the onset of CP.